Development and Application of Structural Communication Grid Tests for Diagnosing Students’ Misconceptions in the Subj - Shahzad Ahmad, Sadia Jamil (JCTE, 2023)
The present study was designed to diagnose student’s misconceptions in learning biodiversity in 9th -grade biology. It is a well-known fact that students come to class with misconceptions based on their previous experiences in the subject i.e. biology. Researchers developed Structural Communication Grids (SCGs) on different biodiversity topics to diagnose misconceptions of students, as they may block their learning in a new situation. Five conceptual areas were selected for constructing SCGs like ‘Biodiversity’, ‘Aims and Principles of Classification’, ‘History of Classification System’, ‘Two-Three Kingdom Classification System’, and ‘Five Kingdom Classification System’. The study was descriptive and quantitative and researchers randomly selected two institutions (one for male and one for female) as a sample of the study. Researchers provided SCGs to 58 students (girls=23, boys=35) to diagnose misconceptions in specific areas. The findings of the study made it clear that almost all students had been confronted with huge misunderstandings about the subject of biology in Grade 9. Researchers suggested that structural communication grids should be developed on other topics of biology and for other subjects (chemistry and physics) to promote students’ meaningful learning by highlighting their misconceptions.